Cracking Control due to Early Thermal Movement of Watertight Continuous RC Members - Risan, Hussam K. (Al-Nahrain Journal for Engineering Sciences, 2017)
Action of applied external loads, early thermal by hydration of cement in reinforced concrete (RC) structures, creep and shrinkage and seasonal effects due to environmental conditions are the main causes of inducing cracks in RC members. Most Design Codes of RC structures have underestimated the distribution steel requirements based on stating nominal or minimum requirements for early thermal and moisture movement especially in watertight continuous constructions. Three dimensional finite element analysis for a verification problem was carried out on a continuous reinforced concrete members with different bar diameter subjected to different applied temperatures values which represent the early-age and seasonal effects. The results of this analysis were compared with the available BS Code equations for crack control for early thermal movements. The comparison between the Code equation and finite element analysis was met in a good agreement. The resulted data was used to study parametrically the crack characteristics in terms of crack width and spacing of RC members in term of the effects of three different construction exposures (Class A, B and C), three values of temperatures with three different bar size diameter (10mm, 12, 16) for each one. The present work was indicated as the bar diameter increases, the required steel ratio increases proportionality to match the assumed crack width. So, to get the minimum steel ratio this is the target. It must use smallest bar diameter. But unfortunately this is limited by minimum practical bar spacing. The overall of present study was indicated that the continuous construction required high steel area especially for class A exposure.